Metamorphosis in modern German literature : transforming bodies, identities and affects - Beaney, Tara (Germanic literatures ;, 2016)
Radical bodily transformation can be shocking, terrifying and wonderful. But what makes it such compelling literary subject matter, and what place does it have in modern Germany? Tara Beaney analyses metamorphosis in literary texts from the Romantic period onwards, focusing on the affects involved. This emphasis allows for a unique insight into ways of experiencing bodily change, into threatened identities, and into changing affective styles across the nineteenth and twentieth centuries. Ranging from canonical texts by E.T.A. Hoffmann and Franz Kafka to the work of post-war and post-Wende writers Marie Luise Kaschnitz and Jenny Erpenbeck, as well as the cross-cultural writer Yoko Tawada, this study shows how narratives of metamorphosis help us negotiate the social and political changes, and the experience of shifting boundaries and identities, that are so pertinent to modern Germany. --